Determinan Faktor Minat Beli Produk Aerostreet - Meidina Riska Maulida (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The development of information and communication technology continues to develop, currently the internet and social media have a big impact on the continuity and convenience of the shopping process. The existence of the internet and social media makes online transactions easier. In this situation, it encourages increased sales and opens up opportunities for local businesses to expand their marketing reach. This research aims to test and analyze the determinants of interest factors in buying Aerostreet products using data collection methods via online Google forms. The type of research used is quantitative research. The sampling technique applied a non-probability sampling technique, namely purposive sampling, determining the criteria for respondents to be consumers of Aerostreet products, aged 17 to 35 years. The analysis used is SEM-PLS, with the Smart PLS 4 application as a data analysis instrument. The research results show that social e-commerce and brand image do not have a significant effect on interest in buying Aerostreet products, while product quality has a significant effect on interest in buying Aerostreet products.